3D Printing of cultured meat products. Issue 1 (2nd January 2022) - K. Handral, Harish; Hua Tay, Shi; Wan Chan, Weng; Choudhury, Deepak
Abstract: Three-dimensional (3D) printing is a fast-developing digital technology with colossal market scope in food and nutrition technology, providing a platform for establishing unique food products with enhanced sensory and nutritional value for a particular end-user. Cultured meat is the concept of producing meat sustainably in laboratory conditions without the sacrifice of animal life and the excessive use of antibiotics. 3D printing could offer unique solutions for the vital issues of cultured meat production; particularly on regulating the protein, fat, and other nutritional content, along with providing realistic texture. This review highlights the immense benefits of 3D printing technology for the scalable and reproducible production of cultured meat products.